Assessment and Comparison of Tongue Posture in Individuals with Different Vertical Facial Patterns - Subrahmanya, Ravi M; Gupta, Swathi (Journal of Orofacial Research, 2014)
Background and objectives: It is established that the posture of the tongue can also influence the dental relationship and facial skeletal pattern of an individual. Hence, this study was designed and planned to assess the posture of tongue in individuals with different skeletal patterns in vertical plane in order to help us to understand the relationship between the tongue posture and the growth pattern of an individual. Materials and methods: Sixty subjects (30 males and 30 females) in the age group of 16 to 20 years were selected as perinclusion criteria. They were divided into two groups (Groups I and II) according to their skeletal pattern in vertical plane based on Jarabak’s ratio and Y-axis. Tongue posture measurements were done using a template based on Rakosi analysis. The data obtained were statistically evaluated by using Mann-Whitney U test (Z test) to test the significance of difference in the tongue posture in subjects with horizontal and vertical skeletal pattern. Results: The dorsum of the tongue was found to be higher in subjects with vertical skeletal pattern at all points. There was no significant difference in the distance between soft palate and root of the tongue. There was no significant difference in the position of tongue tip between the groups. Conclusion: The study supports the existence of a relationship between the posture of the tongue and the skeletal facial pattern in vertical plane.